Derivation of the Energy and Flux Morphology in an Aurora Observed at Midlatitude Using Multispectral Imaging. Issue 5 (21st May 2018) - Aryal, Saurav; Finn, Susanna C.; Hewawasam, Kuravi; Maguire, Ryan; Geddes, George; Cook, Timothy; Martel, Jason; Baumgardner, Jeffrey L; Chakrabarti, Supriya
Abstract: Energies and fluxes of precipitating electrons in an aurora over Lowell, MA on 22–23 June 2015 were derived based on simultaneous, high‐resolution (≈ 0.02 nm) brightness measurements of N 2 + (427.8 nm, blue line), OI (557.7 nm, green line), and OI (630.0 nm, red line) emissions. The electron energies and energy fluxes as a function of time and look direction were derived by nonlinear minimization of model predictions with respect to the measurements. Three different methods were compared; in the first two methods, we constrained the modeled brightnesses and brightness ratios, respectively, with measurements to simultaneously derive energies and fluxes. Then we used a hybrid method where we constrained the individual modeled brightness ratios with measurements to derive energies and then constrained modeled brightnesses with measurements to derive fluxes. Derived energy, assuming Maxwellian distribution, during this storm ranged from 109 to 262 eV and the total energy flux ranged from 0.8 to 2.2 ergs·cm −2 ·s −1 . This approach provides a way to estimate energies and energy fluxes of the precipitating electrons using simultaneous multispectral measurements. Key Point: Auroral energies and fluxes are derived using multi‐spectral imaging